Desperately Seeking ... Relevant Assessment? A Case Study on the Potential for Using Online Simulated Group Based Learning to Create Sustainable Assessment Practices - Anneka Ferguson; Elizabeth Lee (Legal Education Review)
Commentators have questioned whether online instruction is appropriate and effective for practical legal training (PLT), and called for research regarding the incorporation of information and communication technologies (such as online discussions) into PLT. Course evaluations at one PLT site had indicated that students are less satisfied with online discussions than other teaching media. Student satisfaction is relevant to effective learning; satisfaction relates to the affective domain of learning, in which students’ motivation to learn is influenced by their perception of the value of a learning task, and their ability to complete it. This paper reports an exploratory practitioner-initiated study that developed and implemented an online questionnaire to collect data from PLT students in three states, regarding their satisfaction with online discussions. Students’ perceptions of ‘community of inquiry framework’ elements, Marzano and Kendall’s ‘self-system’ factors, and other contextual aspects, were investigated and tested for correlations. The study found student satisfaction with the online discussions was most closely associated with ‘teaching presence’. Students’ satisfaction with student-student interactions was closely associated with ‘self-system’ factors. It is submitted that the PLT lecturer’s role in online discussions should be further investigated to develop and describe evidence-based best practices for PLT.